HUBUNGAN PERILAKU BERESIKO DENGAN KEJADIAN HIV PADA LSL Di KOTA TEGAL - Patriawati Narendra (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Background : HIV prevention activities in MSM in Tegal City state that there are around 100 MSM in Tegal City who carry out HIV screening. The number of HIV / AIDS cases in MSM each year increases every year giving information illustrates that MSM behavior needs to get serious attention so that cases of HIV / AIDS in MSM can be suppressed. Method: This study was conducted to analyze the relationship between risk behaviors and the incidence of HIV in MSM (Male Sex Men) in Tegal City in 2019. Results: This study is a qualitative study, the design used is the Mix Method, to get a broader picture of risky behavior, a qualitative respondents of 10 LSL (Male Sexual Abuse) sexually active to fellow LSL (Male Sex Male). Data collection techniques using in-depth interviews.Conclusion: The ease of technology makes it easy for MSM to get clients, self-defense is weak, does not feel slang makes it difficult for MSM to refuse anal sex invitations which causes an increased risk of HIV incidence among MSM in Tegal City. The need for promotion and education to prevent risky behavior and reduce the incidence of HIV among MSM.Keywords: Risk behaviors, MSM, HIV incidence